626 Studies regarding influences of ethanol on hypoxemic stress in neuroblastoma cells (Balneo and PRM Research Journal, 2024)
Introduction In the modern world a pathology with increasing frequency is that of spinal cord injury (SCI), with the risk of dysfunction on multiple levels. Following our clinical experience, we have conducted studies on the effect of hypoxic stress (also present in spinal cord injury) on neuronal cell cultures treated for a long time with ethanol (trying to reproduce chronic alcoholism). In this article we present the behavior of neural cells subacutely exposed to ethanol after hypoxic stress, in order to perform a comparative analysis with chronic exposure to alcohol. Materials and methods We performed subacute treatments with ethanol in neural cell cultures. We evaluated gene expression and protein synthesis in the case of experimentally induced hypoxic stress. Disscusions The complexity of the human body is superior to experimental models. This experiment creates a model of extremely complex changes after spinal cord injury. The results cannot undoubtedly overlap the conditions of the physiopathological reality. Results and conclusions The model of neural hypoxic suffering in cell cultures is similar in the case of cell cultures treated subacutely with ethanol, except: the risk of neurodegeneration, the phenomenon of axonal die-back, proapoptotic tendencies, proinflammatory tendencies. The effect of chronic (more than acute/subacute) ethanolic consumption seems to determine geno-molecular neural changes with a potentially favorable effect regarding the response (immediate and long-term) to spinal cord injury Keywords: spinal cord injury, alcoholism, hypoxia, neuromuscular recovery